Servitization as a Productive Strategy of a Firm – Evidence from the Forest-Based Industries - Esa Viitamo (The Research Institute of the Finnish Economy (ETLA), 2013)
A central aspect of the industrial evolution in the advanced economies is the phenomenon called servitization. In general, the term servitization or product-service transition is used to highlight the change, where the tangible offering of a manufacturing firm is augmented with intangible services. In this paper, servitization is addressed broadly as a strategic reorientation by a manufacturing firm which entails adjustments in the firm business model as well. A useful framework to address the product-service transition is the socio-economic view of service productivity. On that basis, the paper shows how the productive strategy of the servitizing firm is linked with the business model that builds on service-dominant (S-D) logic. The resources and capabilities of the firm are central drivers in servitization. Via the empirical case study of the servitization strategies in the Finnish forest cluster, the paper extends the scope of analysis in the servitization research from the installed base -industries to the process industries. In a wider context, this paper contributes to the research collaboration between Aalto University (BIT) and Research Institute of the Finnish Economy, ETLA in the field of service research.
Keywords: D24; L14; M11; M21; 330; Servitization; Strategy; Productivity; Service-dominant logic; Forest-based industries; Unternehmensdienstleistung; Geschäftsmodell; Dienstleistungsmanagement; Produktmanagement; Holzindustrie; Finnland